Seagrass contribution to blue carbon in a shallow karstic coastal area of the Gulf of Mexico - Tania C. Cota Lucero; Jorge A. Herrera-Silveira (PeerJ, 2021)
Seagrass meadows provide multiple ecosystem services, including carbon sequestration. However, seagrass meadows are among the most threatened ecosystems worldwide. Determining the magnitude of the carbon stocks in seagrass meadows at the regional scale allows for the estimation of their global magnitude and identification of their importance in regional environmental mitigation strategies. The objective of the present study was to determine the structure of seagrass meadows in the Los Petenes Biosfera Reserve (LPBR) and evaluate their contributions to sinks of carbon in this system, located in Yucatan, which is considered the region with the largest seagrass extension in Mexico. Analyses of the seagrass meadows were executed following standardized protocols (spectral analysis, and isotope and carbon stock analyses). The LPBR stores an average of 2.2 ± 1.7 Mg C ha−1 in living biomass and 318 ± 215 Mg C ha−1 in sediment (top 1 m), and this carbon stock decreases with water depth. The seagrass community extends 149,613 ha, which represents the largest organic carbon stock (47 Tg C) documented in seagrass meadows in Mexico. Macroalgae and seagrass represent 76% of the organic carbon stored in sediment. If LPBR seagrass meadows are lost due to natural or anthropogenic impacts, 173 Tg CO2eqemissions could be released, which corresponds to the emissions generated by fossil fuel combustion of 27% of the current Mexican population. This information emphasizes the importance of seagrass meadows as a carbon sink in the region and their contribution to climate change mitigation, thus allowing for the implementation of necessary conservation strategies.